Petrosavia sakuraii (Makino) J.J.Sm. ex Steenis on Mount Sibuatan, North Sumatra - Ritonga, Yusran Efendi; Tambunan, Muhammad Iqbal H (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2024)
This study presents new findings on Petrosavia sakuraii (Makino) J.J.Sm. ex Steenis, collected from Mount Sibuatan, North Sumatra. P. sakuraii (Makino) J.J.Sm. ex Steenis is a rare mycoheterotrophic plant in Indonesia, and its existance has not been scientifically reported until now. The research was conducted from July to November 2022 in the Gunung Sibuatan Protected Forest, Karo, North Sumatra. Data collection was carried out through exploratory methods. The samples found were documented and identified using various references. The results of the study include descriptions, illustrations, flowering and fruiting periods, habitat, distribution, and conservation status of P. sakuraii (Makino) J.J.Sm. ex Steenis. According to the IUCN Red List, this plant is classified as Data Deficient (DD) due to limited global data. Therefore, this finding contributes to the knowledge of the distribution of P. sakuraii (Makino) J.J.Sm. ex Steenis. This report marks the first recorded presence of this species in North Sumatra, specifically on Mount Sibuatan.